1991
DOI: 10.1177/0148607191015003247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taurine on Total Parenteral Nutrition‐Associated Cholestasis

Abstract: A decrease in the formation/secretion of bile has been well documented in animals on total parenteral nutrition (TPN). Either an excess or an imbalance of amino acids (AA) has been most often implicated. In view of recent work showing that taurine promotes bile flow, bile acid secretion, and protects against hepatotoxic bile acids, the effect of adding taurine (15 mg/dL) to an AA solution was examined in guinea pigs on TPN for 3 days. The TPN-taurine group had a larger bile flow than the group without taurine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 37 publications
(12 reference statements)
1
22
0
Order By: Relevance
“…Theoretically, there are three mechanisms by which prolonged Ta deficit could be implicated in TPN-AC: instability caused by an alteration of hepatic membrane permeability [23,24], decreased antioxidant activity [25][26][27], and tauroconjugation deficiency [19,28,29]. The conjugation of BA seems to make them less toxic, especially Ta-conjugation, although there are differences Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, there are three mechanisms by which prolonged Ta deficit could be implicated in TPN-AC: instability caused by an alteration of hepatic membrane permeability [23,24], decreased antioxidant activity [25][26][27], and tauroconjugation deficiency [19,28,29]. The conjugation of BA seems to make them less toxic, especially Ta-conjugation, although there are differences Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These BA become less toxic when they are conjugated with Ta, and hence the importance of the Ta deficiency that is observed in long-term TPN of the preterm infant, because of either the infant's inability to synthesize it or its deficient administration [15,16]. This would increase the glycoconjugated proportion because the same competitive enzyme mediates conjugation with taurine and with glycine, resulting in the bile becoming more cholestatic [17][18][19]. But Ta has many other functions in the liver (osmoregulation, membrane stability, antioxidant and detoxicant actions, Ca++ regulation...), so that its deficiency could also cause liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first discovery in 1827, a number of studies have been done to find out the various physiological functions and the significance of taurine. It has been reported that taurine has various functions including bile acid production [912], antiarrhythmic effects [1315], and oxidant scavenging effects [16]. In central nervous system, taurine has also been reported to modulate calcium homeostasis [17, 18], neuronal excitabilities [19, 20], and excitotoxic cell death [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Cholestasis is one adverse effect of paren teral nurition (PN), particularly in the new born [1] but also in adults [2], The excess of amino acids [3] or deficiencies of specific ami no acids [4][5][6] have been implicated as factors in the induction of cholestasis. Other physio logical factors such as immaturity of the bili ary secretory system, sepsis, major surgery, short bowel or inflammatory bowel syndrome and malignant disease are associated with a high incidence of PN-related cholestasis [7], Loss of enteral stimulation is another and major factor in the cholestasis associated with PN; however, it is difficult to establish the pri macy of a loss of enteral stimulation over a possible direct toxicity of PN in humans [7], As numerous studies have shown that por tal venous blood flow (PVF) increases if enter al nutrition is given to fasted individuals [8][9][10] and luminant nutrients influence hemo dynamics and oxygenation in the developing intestine [11], it may be that enteral leads cause changes in PVF and portal venous blood gas distribution.…”
Section: Introductionmentioning
confidence: 99%